A Case Report on Relapsed Chronic Lymphocytic Leukaemia with Concomitant Extensive Chronic Graft Versus Host Disease after Allogeneic Haematopoietic Stem Cell Transplantation Successfully Treated with Oral Venetoclax - Teoh, Ching Soon; Goh, Ai Sim (Recent Updates in Disease and Health Research Vol. 9, 2024)
Chronic lymphocytic leukaemia is the most common leukaemia in adults, and it remains an incurable malignancy with conventional chemoimmunotherapy. A middle-aged gentleman who was diagnosed with high-risk chronic lymphocytic leukaemia (CLL), Rai stage IV, Binet C with del(17p) and del(13q) underwent allogeneic haematopoeitic stem cell transplantation (allo-HSCT) from a human leukocyte antigen (HLA) identical sister. Allogeneic haematopoeitic stem cell transplantation remains the only treatment with curative potential but is associated with high non-relapsed mortality (NRM). The patient developed extensive skin, oral, and liver chronic graft versus host disease (GVHD) and required tacrolimus, mycophenolate mofetil (MMF), and prednisolone. In seventh month after allo-HSCT, the patient presented with systemic symptoms, right cervical lymphadenopathy, splenomegaly, marked pancytopaenia, and elevated lactate dehydrogenase (LDH). Bone marrow study, immunophenotyping (IP), chromosome analysis, and PET-CT scan confirmed relapsed CLL with no evidence of Richter’s transformation or posttransplant lymphoproliferative disease (PTLD). Withdrawal of immunosuppressant (IS) worsened cutaneous and liver GVHD. Chemotherapy was not a suitable treatment option in view of immunodeficiency. The patient underwent extracorporeal photopheresis (ECP) therapy eventually for extensive chronic GVHD, and the IS were gradually tapered to the minimal effective dose. The relapsed CLL was treated successfully with oral venetoclax accessible via a compassionate drug program. This case highlights challenges in managing relapsed CLL and loss of graft-versus-leukaemia (GVL) effect despite extensive chronic GVHD. Venetoclax is an effective and well-tolerated oral novel agent for relapsed CLL after allo-HSCT. In conclusion, this study achieved an excellent outcome when treating a patient with relapsed CLL after allo-HSCT using oral venetoclax and concomitant ECP therapy for extensive chronic GVHD. Venetoclax is a well-tolerated oral novel agent and long-term follow-up is important to ensure the disease achieves a sustained complete remission.